Exploring the experiences and perceptions of culinary tourists (Study in Balikpapan City, Indonesia) - Gozali, Gozali (Borneo Novelty Publishing, 2024)
Purpose - This study aims to analyze the evolution, trends, and thematic development in rural tourism research from 2000 to 2024 using a bibliometric approach. Methodology/Design/Approach - Bibliometric analysis was conducted using data retrieved from the Scopus database. Performance analysis and science mapping techniques were applied to identify prolific authors, institutions, countries, citation patterns, and keyword co-occurrence networks. Findings - The analysis reveals a consistent increase in rural tourism publications, with notable contributions from European and Asian countries. Research themes have evolved from economic development and rural revitalization to sustainability, community participation, and digital innovation in tourism. Collaborative networks among institutions and countries have also expanded significantly.Originality/Value - This study provides the first comprehensive bibliometric overview of rural tourism research spanning two decades. It offers valuable insights into the intellectual structure and emerging trends in the field, serving as a reference point for future studies and policy development.